Judicialização da saúde em Mato Grosso - Vieira, Marlene Anchieta (2012)
The objective of this study was to analyze the effectiveness of public policies on citizen's right to health. Because we know that although they are undeniable civilizational achievements of human rights and social recognition and its implementation have demanded historical struggles, so more and more intense. In the specific case of the right to health, despite having all the legal instruments for its realization, we witnessed daily news linked by the media, not on the citizen service as recommended in the art. 6 and 196 of the Federal Constitution of 1988 and Law 8080/93 establishing the Unified Health System - SUS. Dissatisfied citizens have sought mechanisms at their disposal to try to ensure their rights. At this constant demand of the citizen to the courts in pursuit and fulfillment, service assurance and Health System, led the so-called "phenomenon of judicialization of health" which consists of the repeated decisions of the judiciary on the matter, based on compliance the Constitution, in particular regarding the most important asset a person - life itself. A phenomenon that is growing exponentially, becoming not only concern the field of law, but also social service and other areas of applied social sciences as one of the expressions of social issues. Through exploratory research, characterized as bibliographic and documentary stamp quantitative and qualitative, it was found that here in Mato Grosso is the legalization of health and its focus is more on the politics of pharmaceutical care in a demonstration of lack of access to health services . What enabled us to identify the main problems and challenges related to ensuring the right to health of citizens in Mato Grosso, between them is that the effectiveness of the principles of universality and comprehensiveness of access to public health that does not happen as advocated by guidelines SUS since health activities are still centered in large urban centers that do not have the capacity to meet the entire demand.